Writing the famine: the annonary records in Pavia. Years 1258-1260 (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
Global climate change and famine that followed the eruption of Indonesian volcano Samalas stimulated the comune of Pavia to develop a system of registration and assessments necessary to mitigate the effects of the crisis. The measures, modelled using cues from emergency practices already used, stimulated the creation of systems for ascertaining, recording and controlling the availability of grains and their movements, requiring a considerable effort in terms of design skills, economic and human resources used. The practices, tested during the crisis, remained as an acquired patrimony for the administration of the comune, which could also adopt them later in case of need.
Keywords: Crisis; Documentation; Administrative sources; Italian Communal Cities; Provision of food; Provision of supplies; Food supply